2004
DOI: 10.1200/jco.2004.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Palliative Prognostic Score in Hospitalized Patients With Advanced Cancer

Abstract: When oncologists' survival estimates are used, the PaP score is able to identify accurately three isoprognostic patient groups, irrespective of the cancer type. The PaP score may help reduce the uncertainty of formulating a prognosis in patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 26 publications
2
116
0
8
Order By: Relevance
“…These findings highlight a potential role for the mGPS (objective measure) in combination with performance status (subjective measure), with these acting synergistically, predicting survival effectively. This new approach would also enable measures of systemic inflammation to be a part of the routine, clinical prediction of survival in patients with advanced cancer (7,8). A prognostic tool combining mGPS and performance status could guide clinicians in the appropriate cancer treatment for their patients, and further work examining this in practice would be of interest.…”
Section: Resultsmentioning
confidence: 99%
“…These findings highlight a potential role for the mGPS (objective measure) in combination with performance status (subjective measure), with these acting synergistically, predicting survival effectively. This new approach would also enable measures of systemic inflammation to be a part of the routine, clinical prediction of survival in patients with advanced cancer (7,8). A prognostic tool combining mGPS and performance status could guide clinicians in the appropriate cancer treatment for their patients, and further work examining this in practice would be of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that palliative chemotherapy have played significant role in improving patients with advanced cancer quality of life (QoL) or prolonging good QoL for reasonable time (Simmonds, 2000). Surgical intervention for spinal metastases and pathological fractures also proved to improve patients' pain and bring positive impact on overall quality of life to patients with advanced cancer at an acceptable risks (Glare et al, 2004). Symptoms management are known to be achieved by short course radiotherapy for patients with advanced incurable head and neck cancer (Mohanti et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The PaP score contains five parameters (symptom, PS, inflammation, immunity and physician's survival prediction) associated with cancer patient survival. Findings of previous studies have indicated that the PaP score may accurately estimate pre-terminal patient survival (15)(16)(17). Using the PaP score in 44 patients with non-resectable advanced gastric cancer, the correlation between PaP score groups and chemotherapeutic regimens was investigated.…”
Section: Discussionmentioning
confidence: 99%